الفروق اللغوية بين الكلمات المترادفة في المعجم بين يديك من كلمة "عكاز" إلى كلمة "غرز" نموذجا - Gelora Jonson (Rayah Al-Islam, 2018)
The study aimed at uncovering the linguistic differences between the synonyms in the The Arabic Lexicon of “Al-‘Arobi Bayna Yadaik” from the word "عكّاز" (brotherhood) to the word "غَرَزَ" (to receive) – as an example and the knowledge of the proposed benefiting from them in teaching of Arabic for Non Arabic Speakers. The study analytical descriptive method was used based on the analysis of reality and relies on the scientific methods to obtain the information and facts required in the analysis of linguistic differences between these synonyms. As for some of the results obtained from this research are the existence of linguistic differences between words that have synonyms, and each of these words has similarities and different meanings in their use. The suitable method is used to find out the difference and the meaning of the words is by making dictionaries of ancient and modern Arabic as a reference, and can also be through the context of the sentence.